The Gulf and Maghereb Issues in the Postgraduates Research of the Libyan Universities: An Analysis Study of the MA Dissertations at the Faculty of Economics at University of Benghazi - (1982-2008) - العبيدي آمال (Dirasat in Economics and Business, 2011)
This study is concentrated on the research conducted by the postgraduates either males and females at the Libyan Universities. The study mainly concerned with focusing on the Gulf and Maghreb issues in the MA dissertations at the Faculty of Economics at the University of Garyounis. This was mainly done through analyzing the MA Dissertations during the period (1982-2008), in four fields: Economics, Business administration, Accounting and Political Science. The aims of this study are, first is to explore the Gulf and Maghreb issues in the MA dissertations of the postgraduates of the Faculty of Economics. Second, is to identify the general trends according to subjects, tools of data collection and the problems and difficultties facing the process of conducting research. The Criteria of the Analysis used in this paper is based on first; a general survey of the Dissertations during the period of the study. Second, using the Macro Analysis of all subjects instead of focusing on specific topics within each field. The findings of this study showed the lack of interest in dealing with the Arab issues in general and the Gulf and Maghreb issues among the postgraduate research students in most of the departments at the faculty.